"Workhorses of Opportunity": Regional Universities Increase Local Social Mobility - Greg Howard; Russell Weinstein (Institute of Labor Economics (IZA), 2022)
Regional public universities educate approximately 70 percent of college students at four-year public universities and an even larger share of students from disadvantaged backgrounds. They aim to provide opportunity for education and social mobility, in part by locating near potential students. In this paper, we use the historical assignment of normal schools and insane asylums (normal schools grew into regional universities while asylums remain small) and data from Opportunity Insights to identify the effects of regional universities on the social mobility of nearby children. Children in counties given a normal school get more education and have better economic and social outcomes, especially lower-income children. For several key outcomes, we show this effect is a causal effect on children, and not only selection on which children live near universities.
Keywords: J62; I23; I26; R53; 330; economic mobility; regional universities; college attendance